The adolescent experience with parental cancer: effects on roles and responsibilities - Daly, Jennifer Catherine, author; Rosen, Lee A., advisor (Colorado State University. Libraries, 2008)
The majority of research to present has examined the experience of the cancer patient. The experience of children in families coping with parental cancer is an area in need of further exploration. Results of research with this population have been somewhat mixed; however, multiple studies have noted that children coping with parental cancer may experience symptoms consistent with anxiety and depression that may vary by the child's age and gender. Changes in household roles and responsibilities subsequent to a diagnosis of parental cancer have been offered as a possible explanation for these gender and age-related differences. Results of a recent study (Daly, 2005) suggested that time/age of the adolescent may be a primary factor in the increase in household roles and responsibilities during adolescence, rather than the presence of parental cancer. The current research further examined the adolescent experience with parental cancer through ethnographic content analysis of narrative responses regarding household roles and responsibilities. This study utilized original data collected at the same time and from the same sample of undergraduate students in introductory psychology classes at Colorado State University as the Daly 2005 study. Results of the qualitative analysis show that differences were reported for the chores performed by adolescents coping with parental cancer and those who were not coping with parental cancer, with adolescents who were coping with parental cancer for longer than three months generally perceiving themselves as more involved with chores. Results also show that adolescents coping with parental cancer linked their experience of chores with their parent's cancer. The results of the present study are discussed in light of the Daly (2005) study's results and the available body of literature on this topic.
Keywords: adolescent; cancer; child; chores; parent; clinical psychology